Polymer gel dosimetry for neutron beam in the Neutron Exposure Accelerator System for Biological Effect Experiments (NASBEE). Issue 1 (12th January 2015) - Kawamura, H; Sato, H; Hamano, T; Suda, M; Yoshii, H
Abstract: This study aimed to investigate whether gel dosimetry could be used to measure neutron beams. We irradiated a BANG3-type polymer gel dosimeter using neutron beams in the Neutron exposure Accelerator System for Biological Effect Experiments (NASBEE) at the National Institute of Radiological Sciences (NIRS) in Japan. First, the polymer gels were irradiated from 0 to 7.0 Gy to investigate the dose-R2 responses. Irradiated gels were evaluated using 1.5-T magnetic resonance R2 images. Second, the polymer gels were irradiated to 1.0, 3.0, and 5.0 Gy to acquire a depth-R2 response curve. The dose-R2 response curve was linear up to approximately 7 Gy, with a slope of 1.25 Gy −1 ·s −1 . Additionally, compared with the photon- irradiated gels, the neutron-irradiated gels had lower R2 values. The acquired depth-R2 curves of the central axis from the 3.0- and 5.0-Gy neutron dose-irradiated gels exhibited an initial build-up. Although, a detailed investigation is needed, polymer gel dosimetry is effective for measuring the dose-related R2 linearity and depth-R2 relationships of neutron beams.